Some Common Fixed Point Theorems in Menger Spaces Using Occasionally Weakly Compatible Mappings - Rashwan, R. A.; Moustafa, Shimaa I. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper we prove some common fixed point theorems for family of occasionally weakly compatible mappings in Menger space. Also improvement of the results of B. D. Pant and Sunny Chauhan [1] under relaxed conditions is given.